Freeze-thaw cycling impact on the shear behavior of frozen soil-concrete interface - He, Pengfei; Mu, Yanhu; Yang, Zhaohui; Ma, Wei; Dong, Jianhua; Huang, Yongting (Cold regions science and technology, 2020)
The shear behavior of a frozen soil-structure interface plays a vital role in analyzing the performance of engineered structures in cold regions. This study investigates the freeze-thaw cycling impact on the shear behavior of a frozen soil-concrete interface by direct shear tests. Test specimens consisting of a Portland cement concrete disk and frozen loess with an initial moisture content ranging between 9.2% and 20.8% were prepared and conditioned at various sub-zero temperatures (i.e., −1 °C, −3 °C, and − 5 °C) and freeze-thaw (F-T) cycles (i.e., 0, 5, 10, and 20). Experimental results, including shear stress - horizontal displacement curves, the displacements and shear strengths at both peak and residual status, are presented and analyzed. In particular, the influence of F-T cycling on shear behavior is examined. The peak displacement is found to increase linearly with increasing initial moisture content, but their correlation weakens as the number of F-T cycling increases. However, the residual displacement is found to be insensitive to the initial moisture content, temperature, normal stress, and F-T cycling. While the residual friction angle is slightly larger than the peak one before F-T cycling, both gradually increase with an increasing number of F-T cycling. Large cohesion in the peak strength, especially at lower temperatures, completely diminishes in the residual strength due to damage of ice bondage, resulting in a significant shear strength loss between the peak and residual status. The impact of F-T cycling on the interface shear behavior can be attributed to moisture migration toward, formation and accumulation of ice films at the interface. The findings from this study including the shear strength parameters and the displacements at both peak and residual status, can be used to simulate the performance of engineered geotechnical assets such as pile foundations, retaining walls, and earth dams or irrigation channels with concrete linings in cold regions. •Investigate the shear behavior of a frozen soil-concrete interface.•Focus on both shear strength and displacement characteristics.•Examine F-T cycling impact on the shear displacement and strength parameters.•Present key parameters for the simulation of the interface shear behavior.